Intracellular and Extracellular extracts activity of Oscillatoria limnetica and Chroococus minor against some Bacteria and Fangi (Baghdad Science Journal, 2011)
In this study Oscillatoria limnetica and Chroococus minor were isolated ?purified and identification from water canal around Baghdad University Campus. The water of this canals originally from Tigris River. BG-11 culture media was used for their cultivation in suitable laboratory conditions (25c°, 200µE/m2/sec) for 16:8 hrs. Light: dark. Each culture was harvested at the end of exponential phase .Organic solvents used for extraction were Ethanol? Hexane and Methanol 95% to extract the crude active Intracellular and Extracellular substances, and evaporated down to dryness .Antibacterial and antifungal activity of these different extracts were evaluated against 6 strains of gram positive bacteria and gram negative bacteria in addition to fungi, Agar diffusion method was used in this evaluation. Results showed that the extracellular products which extracted by hexane and the extracellular products which extracted by ethanol from Oscillatoria limnetica were have higher antagonistic activity against bacteria and Fungi comparing with methanol extracts .However higher antibacterial and antifungal were obtained against the studied strains of comparing with methanol and ethanol extracts of the same algae products. The gram positive bacteria studied revealed higher susceptibility to attack by the intracellular and extracellular extracts comparing with the gram negative bacteria. These extracts revealed higher antibacterial activity against Bacillus subtilise and the average of inhibition zone were 26, 22 mm. for intracellular and extracellular products of O.limnetica respectively. However, C. minor intracellular products extract has the antagonistic activity against Staphylococcus aureus with 28 mm inhibition zone